Effect of bioengineered nisin on Staphylococcus aureus cells and biofilm - Andre, Cleriane (2019)
Nisin is the most studied lantibiotic, used as a food preservative all around the world, and its structure is composed of five lanthionine rings (A, B, C, D and E). This peptide is characterized by a dual mode of action, consisting of the inhibition of cell wall biosynthesis and the formation of pores in the bacterial cell membrane, due to its ability to interact with the target molecule, lipid II. Due its structure and its gene encoding nature, nisin can be used by bioengineering to generate new derivatives with improved antimicrobial activity. In this study, the molecular structure of nisin A and three derivatives N20P, S29A and M21V were characterized in silico and the antimicrobial effect on S. aureus cells was validated by experimental methods. Sequentially, the antimicrobial activity of nisin A and its derivatives was evaluated against the S. aureus biofilm by detection of the biomass content and metabolic activity using the violet crystal test and 2,3-bis[2- methyloxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide (XTT), respectively. The results obtained by in silico analysis showed that the point mutations caused steric alterations in the nisin molecule, become it more planar, and possibly facilitating the molecular interactions of the C, D and E rings involved in the formation of pores. Cell leakage assays showed greater loss of NADPH and ATP over a short period of time from nisin treated cells. Modifications in the cytoplasmic membrane were observed by analysis of atomic force microscopy. Changes in position 21 of the nisin molecule may result in a peptide with higher activity and greater interaction with membrane molecules, facilitating the formation of pores and promoting greater loss of intracellular ATP. The N20P, S29A and M21V derivatives of nisin A presented greater capacity to inactivate the S. aureus biofilm, both by the removal of cells and inactivation of the sessile cells. The influence of the dltA and mprF genes, which are involved in the cationic peptide resistance mechanism, such as nisin, was also evaluated using the S. aureus ΔdltA and ΔmprF mutants. The deletion of the dltA and xmprF genes did not alter the ability of these strains to form a biofilm, but it made the action of more sensitive to bacteriocins. The results showed the increased antibiofilm potential of modified nisin and suggest that improvement by bioengineering techniques may be a strategy to produce a better antimicrobial to control growth and to remove S. aureus biofilm